Pharmacological Study of Azadirachta indica (Neem) for their possible Antimalarial Activity with Emphasis on Resistance and Resistant Reversal (Journal of Pharmaceutical Negative Results, 2022)
Malaria is one of the deadliest and oldest disease known to mankind for more than 2000 years that causes the death of 0.4 million individuals in 2009. In the era of resistance, multi-drug resistance, finding a new efficacious & potent molecule is always a challenge for Pharmacological science. Researcher across the globe see resistance threat in every molecule. Every drug, molecule whether new or old have resistance possibility. Therefore, researcher in this study tried to understand the behavior of chloroquine-resistant plasmodium yoelii nigeriensis (PYn) which is most experimented & reported animal malaria model equivalent to plasmodium vivax in human with chloroquine & the possibility of resistance reversal for some herbal extracts. 2-20 times chloroquine doses (10-100 mg/ kg) are not able to produce sufficient efficacy in chloroquine resistant PYn. Where 5 mg/ kg dose of chloroquine is effective dose against the chloroquine sensitive dose. Same while, most of the plant extracts are also not able to produce minimal therapeutic response on Chloroquine resistant plasmodium when given alone. However, plant extracts Azadirachta indica (AI) at 300 mg/ kg & 1000 mg/ kg shows a better effect when given with chloroquine 20 mg/ kg then alone. Out of all plant extracts hydroalcoholic extracts of dried leaves & ethanolic extract of dried bark of AI. Current approach of multi-drug dosage supports also supported here in the study with a thought of using antimalarial plant extracts during regular malaria treatment. Genesis of idea of referring standardized plant extract(s) in combination as oral dosage with prophylactic (travelers) malaria & malaria treatment or side-food for malaria will also possible. Positive results may pave a path for inclusion of herbal extracts or herbs as side treatment or drug resistance-breaker food for malaria.